Analisis Kasus Tindak Pidana Penganiayaan dari Sudut Pandang Viktimologi: Studi Kasus Putusan Nomor 695/Pid.B/2024/PN SRG - Nurul Fadilah; Nadiah Nurfasyah; Ipeka Feodora Skatata G; Monica Natasya Silitonga; Muhammad Lutfi Styabudi (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Assault is a criminal act intentionally committed to cause pain, physical injury, or damage to another person. As a state governed by law, efforts to address assault crimes are necessary as part of law enforcement. However, existing regulations focus mainly on the perpetrators, and there is a need for regulations that also focus on the victims, examined through the perspective of victimology. The purpose of this study is to give greater consideration to the victim's side in a criminal act, how victims are more heavily impacted, and the legal protection that remains insufficiently fulfilled. This research uses a theoretical study with the approach of victimology theory and restorative justice theory. It employs a normative empirical method with secondary data, based on legislation. The results of this study show that victims of assault crimes suffer impacts in every aspect, including physical injuries, psychological disturbances, economic effects, and social life disruption. Victims of assault should receive protection from the victimology perspective, such as restitution or compensation, counseling assistance, medical aid, and legal support. However, these protections have not been adequately fulfilled. This is illustrated by case number 695/Pid.B/2024/PN SRG, where the defendant was sentenced under Article 351 paragraph (2) for assault causing serious injury to the victims, with a prison sentence of 1 year and 10 months plus a court fee of Rp. 2,000 (two thousand rupiah). Considering the victims experienced terror before the incident and multiple stabbing actions resulting in physical and psychological harm, the victims are entitled to restitution, counseling, and adequate legal assistance. Yet, in reality, such protections remain unmet.